Implementasi Model Pembelajaran Problem Based Learning Di Sekolah Dasar - Sriyatno, Sriyatno (Universitas Sebelas Maret, 2020)
One of the factors supporting the success of a learning is the application of the right learning model. The learning model is a conceptual framework about systematic procedures in organizing learning experiences to achieve learning objectives, both for students and teachers. The aims of this research are: 1. To describe the meaning of Problem Based Learning learning model. 2. Describe the syntax of Problem Based Learning. 3. Describe the strengths and weaknesses of the Problem Based Learning model. The results of this study are: 1. Problem Based Learning is a learning model that exposes students to real world problems to start learning and is one of the innovative learning models that can provide active learning conditions for students. 2. PBL syntax includes: student orientation to problems. Organizing students, guiding individual/group investigations, developing and presenting results, analyzing and evaluating problem solving processes.